A general, enantioselective synthesis of 2-substituted thiomorpholines and thiomorpholine 1, 1-dioxides. Issue 40 (3rd October 2019) - Reed, Carson W.; Lindsley, Craig W.
Graphical abstract: Highlights: First enantioselective methodology for chiral, C2-subsituted thiomorpholines. Rapid access to chiral thiomorpholine 1, 1-dioxides. Control of stereochemistry based on organocatalyst employed. General protocol affording high % ee. Abstract: In the course of our drug discovery programs, we had need to access chiral, 2-substituted thiomorpholines and their oxidized congeners, thiomorpholine 1, 1-dioxides. Here, we disclose a high-yielding, general protocol for the enantioselective synthesis of C2-functionalized thiomorpholines and thiomorpholine 1, 1-dioxides.